Currículo crítico? Uma investigação acerca do currículo paulista de geografia no Enisno Médio - Lomardo, Juan (Universidade Federal de São Carlos, 2017)
The main object of this research is the geography curriculum of the public High School system of Sao Paulo, more precisely its theoretical reference. Based on the analysis of such curriculum, the aim is to check the accuracy of the categories of Critical Geography, in order to test how the concept of criticism is applied, as well as unveil politics questions that come up in the shape of such investigation. Its theoretical background are the subsidies offered by Critical Theory and by scientific developing of this way of thinking, to the educational and curriculum area.
Is this a critical curriculum? An investigation about the high school geography curriculum of São Paulo state.
Keywords: Currículo; Geografia; Geografia Crítica; Teoria Crítica; Education - Curricula; Geography - Study and teaching; Critical theory; CIENCIAS HUMANAS::EDUCACAO